2023
DOI: 10.3390/ijms242015349
|View full text |Cite
|
Sign up to set email alerts
|

Trichoderma viride Colonizes the Roots of Brassica napus L., Alters the Expression of Stress-Responsive Genes, and Increases the Yield of Canola under Field Conditions during Drought

Zuzanna Garstecka,
Marcel Antoszewski,
Agnieszka Mierek-Adamska
et al.

Abstract: In this work, we present the results of the inoculation of canola seeds (Brassica napus L.) with Trichoderma viride strains that promote the growth of plants. Seven morphologically different strains of T. viride (TvI-VII) were shown to be capable of synthesizing auxins and exhibited cellulolytic and pectinolytic activities. To gain a deeper insight into the molecular mechanisms underlying canola–T. viride interactions, we analyzed the canola stress genes metallothioneins (BnMT1-3) and stringent response genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 116 publications
0
1
0
Order By: Relevance
“… Wang et al (2018) observed that T. viride biofertilizer reduced NH 3 volatilization in alkaline soil and enhanced the growth of sweet sorghum. Garstecka et al (2023) discovered that T. viride could colonize roots and increase the yield of Canola under drought conditions. Metwally and Soliman (2023) found that T. viride inoculation alleviated the salt stress of tomato seedlings and maintained their normal growth.…”
Section: Introductionmentioning
confidence: 99%
“… Wang et al (2018) observed that T. viride biofertilizer reduced NH 3 volatilization in alkaline soil and enhanced the growth of sweet sorghum. Garstecka et al (2023) discovered that T. viride could colonize roots and increase the yield of Canola under drought conditions. Metwally and Soliman (2023) found that T. viride inoculation alleviated the salt stress of tomato seedlings and maintained their normal growth.…”
Section: Introductionmentioning
confidence: 99%